Zeolitic-Imidazolate Frameworks Enhanced Surface Plasmon Resonance Sensor for Organic Dyes Sensing - Azeman N.H.; Zain A.R.M.; Daniyal W.M.E.M.M.; Jamil M.S.M.; Bakar M.H.A.; Nazri N.A.A.; Khushaini M.A.A.; Mokhtar M.H.H.; Bakar A.A.A. (Institute of Electrical and Electronics Engineers Inc., 2025)
This work highlights the development of zeolitic-imidazolate frameworks 8 (ZIFs-8) to enhance surface plasmon resonance (SPR) sensor for methylene blue compound detection. ZIF-8 was synthesized via the solvothermal method. XRD results show the appearance of diffraction peaks at 2?= 7.4, 10.4, 12.7, and 18.0, which are assigned to 011, 002, 112, 022, 013, and 222 lattice planes, respectively, confirming the high crystalline ZIF-8 produced. The X-ray photoelectron spectroscopy (XPS) analysis exhibits the presence of C, O, Zn, and N elements on the surface of the ZIF-8 structure. Methylene blue was detected through the donor-acceptor interaction of a lone pair of Zn atoms in ZIF-8 with methylene blue. These two materials can also interact through - interactions because both ZIF-8 and methylene blue possess aromatic rings in their structure. The FESEM characterization shows a uniform particle size produced on a surface of Au thin film in the 100-130-nm range. A good sensitivity of 1.3821 ppm-1 with a detection and quantification limit of 0.92 and 2.79 ppm, respectively, was obtained for the SPR sensor using ZIF-8 as a sensing material at a low methylene blue concentration range in comparison to bare Au. Nonetheless, the steepness of the graph started to decline after 1 ppm methylene blue concentration due to the fully occupied active sites on the surface of ZIF-8. In the selectivity study, a prominent SPR shift was observed when ZIF-8 interacted with methylene blue, compared to other interferences, proving that ZIF-8 has a good selectivity toward methylene blue. ? 2001-2012 IEEE.